2022
DOI: 10.1111/ijd.16333
|View full text |Cite
|
Sign up to set email alerts
|

Where are the older adults? Age distribution of nail psoriasis randomized clinical trials’ participants: a systematic review

Abstract: Where are the older adults? Age distribution of nail psoriasis randomized clinical trials' participants: a systematic review Dear Editor, Nail involvement is common among psoriasis patients, with an estimated lifetime incidence approaching 90%. 1 Psoriasis has a bimodal age incidence, peaking at 30-39 and 60-69 years. Therefore, nail psoriasis (NP) is an important disease among older adults. 1 It is unknown whether therapeutic safety and efficacy data from NP clinical trials pertain to this population. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Systemic therapies should be considered if NP is severe, involves many fingernails/toenails and with joint involvement [ 57 , 58 ]. Older adults are underrepresented in NP randomized clinical trials, thus recruitment of this population in research studies are needed to establish applicable NP treatment guidelines [ 59 ].…”
Section: Inflammatory Nail Changesmentioning
confidence: 99%
“…Systemic therapies should be considered if NP is severe, involves many fingernails/toenails and with joint involvement [ 57 , 58 ]. Older adults are underrepresented in NP randomized clinical trials, thus recruitment of this population in research studies are needed to establish applicable NP treatment guidelines [ 59 ].…”
Section: Inflammatory Nail Changesmentioning
confidence: 99%
“…4 Ricardo et al analyzed 45 studies on pharmacologic treatments for nail psoriasis in order to characterize age distribution and participation of older adults. 3 The authors reported that 30 studies (66.67%) did not have an upper age limit. However, of these, only eight (26.7%) studies reported a number of participants over 65 years old, accounting for an average participation of 5.8%.…”
mentioning
confidence: 99%
“…2 Indeed, comorbidities, polypharmacy, drug interactions, and side effects are more frequent as well as conventional systemic treatments (methotrexate, cyclosporine, and acitretin) are often contraindicated and show a higher risk of adverse events or drug interactions. 2 We have read with great interest the article recently published by Ricardo et al 3 entitled "Where are the older adults? Age distribution of nail psoriasis-randomized clinical trials' participants: a systematic review" presenting a sub-analysis of a systematic review assessing the ethnoracial composition of randomized clinical trials.…”
mentioning
confidence: 99%
See 2 more Smart Citations